Hibiscus rosa-sinensis flower extract-mediated fabrication of zinc oxide nanoparticles, characterization and its antimicrobial activity - Komal Thakur; Avneet Kaur (Pharmacological Research - Modern Chinese Medicine)
Introduction: Hibiscus rosa-sinensis commonly known as Zhū Jǐn Huā' (朱槿花) which is widely beings used in Traditional Chinese Medicine (TCM) in the form of herbal preparations and decoctions for the ailment of inflammations, skin infections, and gynecological disorders. Zhū Jǐn Huā' (朱槿花) is well known for its good phytochemicals composition including anthocyanins, flavonoids and other bioactive components making it a promising choice for linking traditional Chinese medical knowledge with modern nanotechnology. Method: ZnO NPs (Zinc oxide nanoparticles) were fabricated following simple chemical precipitation method using aqueous flower extract (Hibiscus rosa-sinensis). Phytochemical screening of flower extract was done to identify bioactive components. Fabricated nanoparticles were characterized through Scanning Electron Microscopy (SEM), Transmission electron Microscopy (TEM), Energy Dispersive Spectroscopy (EDS), X-ray Diffraction (XRD), and Fourier-Transform Infrared Spectroscopy (FT-IR) to analyze their morphology, size, crystallinity, and elemental composition. Further, antimicrobial activity was evaluated against Escherichia coli and Rhizopus species. Results: Phytochemical analysis of studied flower extract confirmed the presence of flavanone, coumarins, flavonoids, steroids, and anthocyanins in the flower extract. Characterization results demonstrated that the ZnO NPs were crystalline with an average size ranging from 7 to 14 nm, as revealed by XRD analysis. EDS confirmed the elemental composition of the nanoparticles. Antimicrobial assay observation indicates a good antibacterial and antifungal activity in fabricated ZnO NPs against E. coli and Rhizopus species, respectively. Discussion: The present work revealed the successful green synthesis of ZnO NPs using H. rosa-sinensis flower extract and highlights the potential of its specific bioactive components documented in traditional Chinese medicine. The nanoparticles exhibited desirable properties with a good antimicrobial potential, suggesting their potential application in biomedical and environmental fields.